2013
DOI: 10.11607/ortho.870
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of enamel demineralization during orthodontic treatment:
An in vitro comparative study

Abstract: The use of these commercially available medicaments could prove to be beneficial for patients undergoing orthodontic treatment and who are at a risk for developing enamel decalcification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Hamba et al 22 reported minimum loss of minerals and shallowest lesions in the fluoride group compared to CPP-ACP and CPP-ACP-F. 22 The preventive effects of CPP-ACP, MI Paste Plus, fluoride varnish and sodium-calcium-phosphosilicate were compared in another study and it was found that fluoride varnish was the most effective of all. 21 Another study confirmed the optimal efficacy of fluoride for prevention of WSLs. 27 Several clinical and in vitro studies have documented that fluoride-containing products have the greatest remineralizing effect compared to other products.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Hamba et al 22 reported minimum loss of minerals and shallowest lesions in the fluoride group compared to CPP-ACP and CPP-ACP-F. 22 The preventive effects of CPP-ACP, MI Paste Plus, fluoride varnish and sodium-calcium-phosphosilicate were compared in another study and it was found that fluoride varnish was the most effective of all. 21 Another study confirmed the optimal efficacy of fluoride for prevention of WSLs. 27 Several clinical and in vitro studies have documented that fluoride-containing products have the greatest remineralizing effect compared to other products.…”
Section: Discussionmentioning
confidence: 87%
“…However, in some previous studies, MI Paste Plus significantly inhibited the formation of enamel lesions, although its efficacy was still lower than that of fluoride in this respect. 21-23 This controversy in the results might be attributed to differences in methods of assessment of samples since we only measured the surface microhardness using a Vickers microhardness tester while previous studies used polarized light microscope and micro-computed tomography for precise quantification of mineral loss and measurement of depth of lesions. 21,23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Conversion of carbonic acid into water and carbon dioxide should occur before any of these circumstances undergoes alterations. [28][29][30]…”
Section: Concept Of Remineralizationmentioning
confidence: 99%
“…The description of each study is provided in Appendix II. In total, 15 articles [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] were excluded, six [20][21][22][23][24][25] because the experimental design used artificial lesions in vitro, two 26,27 because there was no comparison of a remineralising intervention against a control. The participants of one study 28 had not undergone orthodontic treatment, one study 29 did not include statistical data in the results section and was therefore excluded since a meta-analysis or comparison of results could not be performed.…”
Section: Study Characteristicsmentioning
confidence: 99%